Akibat Hukum Pewarisan Adat Tunggu Tubang pada Suku Semendo - Tsania Manzil Assolich; Talitha Nabilah; Achmad Ichsan Maliki; Wiwin Yulianingsih (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Inheritance law is actually part of civil law. One of the systems of inheritance for the adat waiting for tubang is implemented in the Semendo Tribe, South Sumatra. The customary inheritance law system in Indonesia is influenced by differences in kinship arrangements in society which are illustrated by the existence of patrilineal, matrilineal and parental systems of descent. Based on this, then it is worth exploring regarding the implementation of the Wait Tubang inheritance in the Semendo Tribe in the customary inheritance system in Indonesia as well as legal consequences for assets and their heirs. This research is an urgency to be carried out, in order to provide an understanding of legal certainty regarding the customary inheritance system from a civil or nationally applicable legal perspective, in which legal certainty can become a provision for further research. This research is normative juridical type. Approach to statutory regulations and concept approach used in this study. The results of the study found that the application of the legal system of customary inheritance for the Semendo tribe is inherent in the matrilineal descent system, where the first daughter is